Late Quaternary Sedimentation History of the Lena Delta. - Schwamborn, Georg; Rachold, Volker; Grigoriev, Mikhail N (PANGAEA, 2002)
Core and outcrop analysis from Lena mouth deposits have been used to reconstruct the Late Quaternary sedimentation history of the Lena Delta. Sediment properties (heavy mineral composition, grain size characteristics, organic carbon content) and age determinations (14C AMS and IR-OSL) are applied to discriminate the main sedimentary units of the three major geomorphic terraces, which form the delta. The development of the terraces is controlled by complex interactions among the following four factors: (1) Channel migration. According to the distribution of 14C and IR-OSL age determinations of Lena mouth sediments, the major river runoff direction shifted from the west during marine isotope stages 5-3 (third terrace deposits) towards the northwest during marine isotope stage 2 and transition to stage 1 (second terrace), to the northeast and east during the Holocene (first terrace deposits). (2) Eustasy. Sea level rise from Last Glacial lowstand to the modern sea level position, reached at 6-5 ka BP, resulted in back-filling and flooding of the palaeovalleys. (3) Neotectonics. The extension of the Arctic Mid-Ocean Ridge into the Laptev Sea shelf acted as a halfgraben, showing dilatation movements with different subsidence rates. From the continent side, differential neotectonics with uplift and transpression in the Siberian coast ridges are active. Both likely have influenced river behavior by providing sites for preservation, with uplift, in particular, allowing accumulation of deposits in the second terrace in the western sector. The actual delta setting comprises only the eastern sector of the Lena Delta. (4) Peat formation. Polygenetic formation of ice-rich peaty sand (''Ice Complex'') was most extensive (7-11 m in thickness) in the southern part of the delta area between 43 and 14 ka BP (third terrace deposits). In recent times, alluvial peat (5-6 m in thickness) is accumulated on top of the deltaic sequences in the eastern sector (first terrace).
Sedimentation and mineral analysis on sediment cores from the Lena Delta
Keywords: Arga Island; AWI_PerDyn; ChekanovskyHighl; HAND; Laptev Sea System; LD00-1316-1; LD00-1316-2; LD00-1316-3; LD98-D01; LD98-D06; LD98-D07; LD98-D08; LD98-D10; LD98-S04; LD98-S05; LD98-S06; Lena-Delta1998; Lena-Delta1999; Lena-Delta2000; LSS; Nikolay Lake, Lena Delta, Russia; Olenyok Channel; PERM; Permafrost Research (Periglacial Dynamics) @ AWI; PG1440; RCD; Rotary core drilling; Samoylov Island, Lena Delta, Siberia; Sampling by hand; Sampling on land; Sampling permafrost; Sardakh Channel; Seismic, shallow profile; SEISS